Role of the staff in prevention of hospital-acquired infections - Gierasimovič, Zita; Karpovič, Alina (Slauga. Mokslas ir praktika, 2020)
The aim. To assess maintenance of environmental surfaces and its significance to transmitting hospital-acquired infections.Materials and methods. A six-month investigation in one of Vilnius university hospitals was carried out seeking to assess hygiene of environmental surfaces in surgical units. The summarised investigation results are presented. A testing set (a seal, a fluorescent lamp, a source of light) was used to assess hygiene of the surfaces. Surface testing was carried out every two months (three times in all).Results, conclusions: A total of 23.0% of violations of maintenance of frequently touchable surfaces has been established. In the course of testing, the number of mistakes in maintenance of care equipment decreased by as much as 7.2%. Violations of maintenance of surfaces of liquid soap dispensers were frequent; they accounted for 23.6 %. The least amount of violations in the staff environment were related to the use of equipment and tissue cases. In most cases priority was given to maintenance of care equipment. More than one fourth of violations in the patient environment were established in the sphere of frequently touchable surfaces. One fourth of violations found in the patient environment were related to the maintenance of surfaces of the screens, bed frames, and liquid soap dispensers. Observation and the analysis of violations reduced contamination of the surfaces of care equipment by as much as twice; however, they had the least effect on maintenance of frequently touchable surfaces.
Keywords: care equipment; surfaces of the patient; staff environment